Optimum Age of Starter for Microbial Transglutaminase (MTGase) Production Produced by Streptomyces thioluteus TTA 02 SDS 14 and Characterization of Crude Enzyme - Dewi Seswita Zilda; Yusro Nuri Fawzya; Lia Siti Nur'amaliyah; Hana Nurullita Prestisia; Nisa Rachmania Mubarik; Puspita Lisdiyanti (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
The condition of starter plays important role in enzyme production. Optimum starter will lead to the optimum yield of enzyme production. The experiments which were aimed to obtain the optimum  age for starter of Streptomyces thioluteus TTA 02 SDS 14  from solid as well as liquid medium had been carried out which would be used for transglutaminase production. Medium used for culture maintenance, starter optimization and enzyme production was described by Bahrim. The result showed that S. thioluteus TTA 02 SDS 14 was ready to be used as starter after being cultured  on solid medium continued in liquid medium each  for 6 days. The enzyme production in a bioreactor using optimized starter produced enzyme with the highest activity after being fermented for 2 days with 150 rpm agitation. The crude enzyme active optimally at 45-50 oC, pH of 6 and  no effect of metal ion and inhibitor on enzyme activity.